1984
DOI: 10.1515/cclm.1984.22.11.717
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Aldosterone, Cortisol and Electrolyte Concentrations in Physical Exercise after Magnesium Supplementation

Abstract: Plasma aldosterone, cortisol, sodium (Na), potassium (K), calcium (Ca), magnesium (Mg) äs well äs urine and sweat Na, K, Ca and Mg concentrations were measured in nine male healthy persons during an one hour ergometer exercise before and after a fourteen day magnesium aspartate (Mg) Supplementation. The usual aldosterone and cortisol increase during exercise was not observed and cortisol concentration was significantly lowef after Mg Supplementation. Na and K in plasma increased during the exercise; these chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
(4 reference statements)
0
17
0
Order By: Relevance
“…Magnesium supplementation (15 mmol magnesium-L-aspartate-hydrochloride) taken daily for 14 days produced a change in hormonal response to a 1 h ergometric exercise (Golf et al, 1984). Specifically, aldosterone and cortisol did not increase in response to the exercise after the supplementation period.…”
Section: Calciummentioning
confidence: 97%
“…Magnesium supplementation (15 mmol magnesium-L-aspartate-hydrochloride) taken daily for 14 days produced a change in hormonal response to a 1 h ergometric exercise (Golf et al, 1984). Specifically, aldosterone and cortisol did not increase in response to the exercise after the supplementation period.…”
Section: Calciummentioning
confidence: 97%
“…In studies of Golf et al, it was demonstrated that this process can be limited by supplementation of athletes' diet with magnesium. After completion of the 14-day cycle of supplementation with 15 mol of magnesium was recorded lack of exercise-induced increase in cortisol level [59]. Action of magnesium is explained by its inhibitory activity on NMDA (N-metil-d-aspartate) receptor, which leads to reduction in adrenocorticotropin secretion by anterior pituitary and to inhibition of cortisol synthesis at the stage of conversion of cholesterol to pregnenolone [60].…”
Section: Dietary Supplementsmentioning
confidence: 99%
“…Elevation of plasma CS and increased urinary excretion of CS and its metabolites have been reported in monkeys subjected to anxiety or aggression [7], and in humans under emotional and physical stresses [2,[8][9][10].…”
Section: Stimulation By Stress Of Secretion Of Catecholamines and Cormentioning
confidence: 99%
“…Plasma Mg was unchanged, but rbc Mg decreased sig nificantly during exercise on an ergometer in a study by Golf et al [10]. Boehmer [220], however, found that an hour's strenuous exercise sharply lowered serum Mg in a large group of well-trained athletes whose resting serum Mg values were normal.…”
Section: Short-term Intensive Exercise and Magnesiummentioning
confidence: 99%